How boarding house entrepreneurs recover after thecovid-19 pandemic - Vika Sari Kusbiyanto; Dewi Kusumowati (University of Merdeka Malang, 2024)
This research aims to examine the effect capital, condition of the place, strategic location and promotions on income of boarding house entrepreneurs in Semarang City. The type of this research is quantitative descriptive. Data used in this research is quantitative data, obtained from respondents. The data source is primary data obtained through questionnaires which are distributed directly to boarding house owners. The sample is 41 boarding house entrepreneurs in Semarang. This research uses linear regression analysis using SPSS with the results that capital, condition of the place, strategic location and promotions has an effect on income.